Effects of Physical Education Activity Management Using the Sport of Lacrosse on Skill-Related Physical Fitness and Sportmanship of Lower Secondary School Stydents - Chithan, Tanayuth; Samawathdana, Rungrawee (An Online Journal of Education, 2021)
The purpose of this research was to study the effects of physical education activity management using the sport of lacrosse on skill-related physical fitness and sportsmanship of lower secondary school students. The effects of the sport of lacrosse were studies by; 1) comparing the mean scores of skill-related physical fitness before and after implementation between the experimental group and the control group, 2) comparing the mean scores of sportsmanship before and after implementation between the experimental group and the control group. The samplings were 60 lower secondary school students who volunteer to participate on this study. There were two, experimental and control groups of 30 students for each group. The research instruments were lessons plan, skill-related physical fitness test and sportsmanship test. The validity was using Index of Item Objective Congruence was 0.90, and reliability was 0.83. The data were analyzed by means, standard deviations and t-test. The research findings were; 1) The mean scores of the skill-related physical fitness before the experiment between the experimental and the control were not significantly difference at .05 level. Meanwhile, after the experiment the study found that the means scores of the experimental group was higher than the control group with significantly difference at .05 level. 2) The mean scores of the sportsmanship before the experiment between the experimental and the control were not significantly difference at .05 level. Meanwhile, after the experiment the study found that the means scores of the experimental group was higher than the control group with significantly difference at .05 level